2008
DOI: 10.1080/02652040802193006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel nanocapsule formulation by emulsion-diffusion combined with high hydrostatic pressure

Abstract: A common method used to prepare polymeric nanoparticles in pharmaceutical technology is emulsion-diffusion. However, this method has several disadvantages due to the long duration of the process. At the diffusion step of conventional emulsion-diffusion, high pressure treatment could replace the addition of great quantities of water resulting in diffusion of the solvents from the internal phase to the external phase. The objective of the present study was to develop a novel method for nanoparticle formulation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The morphology and structure of the nanocapsules were analyzed by scanning electron microscopy. The results showed that β-cyclodextrin can be used as a cryoprotectant to maintain the physical stability of eugenol and protect eugenol from freezing damage [85].…”
Section: Polysaccharide-based Biopolymersmentioning
confidence: 99%
“…The morphology and structure of the nanocapsules were analyzed by scanning electron microscopy. The results showed that β-cyclodextrin can be used as a cryoprotectant to maintain the physical stability of eugenol and protect eugenol from freezing damage [85].…”
Section: Polysaccharide-based Biopolymersmentioning
confidence: 99%
“…The subsequent addition of water in the emulsion induces solvent diffusion from the dispersed phase to the continuous phase, resulting in the formation of ''nanospheres (matrices)" or ''nanocapsules (liquid embedded in a wall material)" (Quintanar-Guerrero, Fessi, Allémann, & Doelker, 1996). This technique is performed using biopolymers, such as poly-D,L-lactic acid (PLA) Quintanar-Guerrero et al, 1996) and polycaprolactone (PCL) (Lee, Min, Bourgeois, & Choi, 2008). The advantages of this formulation are high yields of encapsulation, high reproducibility, better particle size control, and the ease of scaling up production (Moinard, Chevalier, Briançon, Beney, & Fessi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ten milliliters of the emulsions were placed in a 15 mL centrifuge tube (1.5 cm interior diameter x 12 cm length) and stored for 1 month. Then, it was centrifuged at 3,000 rpm for 20 min to measure the creaming index (Lee, Min, Bourgeois, & Choi, 2008). The height of the emulsion was measured by a ruler and calculated as the percentage of emulsion height per total height of solution according to Eq.…”
Section: Emulsion Stabilitymentioning
confidence: 99%